Kepastian Hukum melalui Perancangan Kontrak Kerja Pasca Akuisisi Perusahaan (Studi Putusan MA Nomor 707 K/Pdt.Sus-PHI/2016) - Hafila Azzafi Daskarata; Wisnu Indra Setiawan; Maulana Iqbal Adiyatma; Rayi Kharisma Rajib (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research examines the urgency of legal certainty in employment contracts after corporate acquisition, using the Supreme Court Decision No. 707 K/Pdt.Sus-PHI/2016 as the main reference. The increasing trend of acquisitions in Indonesia often creates disputes regarding the continuity of employment status, normative rights, and compensation, particularly for workers with permanent employment agreements (PKWTT). This study employs a normative juridical approach, focusing on statutory regulations, doctrines, and relevant jurisprudence to analyze the extent to which employment contracts can guarantee legal certainty for workers and companies post-acquisition. The findings show that acquisition cannot be used as a basis for terminating employment relationships unilaterally without fulfilling workers’ rights, and employment contracts must contain clauses ensuring continuity of employment, protection of normative rights, and clear dispute resolution mechanisms. The involvement of notaries and advocates is also essential in ensuring the formal legality and substantive fairness of employment contracts. This study contributes to the development of labor law by emphasizing the importance of contract drafting as a legal instrument to balance corporate efficiency with the protection of workers’ rights.